Strategi Manajemen Meningkatkan Mutu Pegawai pada Kantor Kementerian Agama Kota Makassar - Ahmad, Hadiah (JURNAL ILMIAH GEMA PERENCANA, 2024)
This policy paper describes the management strategy implemented the Ministry of Religious Affairs Office of Makassar City to improve the quality of employees. This paper uses a qualitative approach with a case study method, where data is obtained through in-depth interviews with key informants, participant observation, and documentation. The results of this article show that the management strategy implemented the Ministry of Religious Affairs Office of Makassar City is not optimal in improving the quality of employees and has not been able to create a professional work culture. Factors that cause less than-optimal management strategies include a lack of training and development for employees, not yet optimal planning and organizing systems, and an unsupportive organizational culture. Thus, the author recommends that the Head of the Ministry of Religious Affairs Office of Makassar City create a Memorandum of Understanding (MoU) and Cooperation Agreement (PKS) between the Ministry of Religious Affairs Office of Makassar City and the Research and Development and Religious Education and Training Center the Ministry of Religious Affairs of South Sulawesi for development and training; proactively providing everything related to complete office facilities and infrastructure; create a Circular on the implementation of the "Employee Performance Assessment System (SISJAPEG)" application; and create a Circular to produce Employee Performance Reports periodically (monthly) with rewards for outstanding employees.